2012
DOI: 10.1210/jc.2011-2391
|View full text |Cite
|
Sign up to set email alerts
|

Human Melatonin and Alerting Response to Blue-Enriched Light Depend on a Polymorphism in the Clock Gene PER3

Abstract: We provide first evidence that humans homozygous for the PER3 5/5 allele are particularly sensitive to blue-enriched light, as indexed by the suppression of endogenous melatonin and waking theta activity. Light sensitivity in humans may be modulated by a clock gene polymorphism implicated in the sleep-wake regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 17 publications
5
77
1
Order By: Relevance
“…Moreover, the sleepreducing effects of mutant PER3 are light dependent (observed only in LD and not in DD). Consistent with our findings, it has been suggested that a polymorphism in PER3 is involved in modulating the alerting effects of light and the influence of light on sleep in human subjects (38,39).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the sleepreducing effects of mutant PER3 are light dependent (observed only in LD and not in DD). Consistent with our findings, it has been suggested that a polymorphism in PER3 is involved in modulating the alerting effects of light and the influence of light on sleep in human subjects (38,39).…”
Section: Discussionsupporting
confidence: 92%
“…Short wavelengths are very effective in suppressing melatonin production, which is wavelength dependent [55,56]. In human [57,58] and animals [59,60], pineal melatonin production is highly photosensitive to light of short wavelength (i.e. blue light).…”
Section: Melatonin Suppressionmentioning
confidence: 99%
“…Together with light's wavelength, other properties, such as intensity, duration, and timing, are crucial in determining its effects on human physiology and behavior (for a review, see Cajochen, 2007). Nighttime light exposure triggers melatonin suppression with concomitant reduction of subjective sleepiness and objective markers of sleepiness (e.g., waking electroencephalographic [EEG] theta activity, incidence of slow eye movements) (Cajochen et al, 2000;Chellappa et al, 2011bChellappa et al, , 2012Lockley et al, 2006;Ruger et al, 2005). It has been suggested that these effects are mediated through melatonin's alerting effects and/or its resetting properties on the endogenous circadian pacemaker (Chellappa et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%